Subnational sustainable development: The role of vertical intergovernmental transfers in reaching multidimensional goals. (October 2022) - Guerrero, Omar A.; Castañeda, Gonzalo; Trujillo, Georgina; Hackett, Lucy; Chávez-Juárez, Florian
Abstract: From a public finance point of view, achieving sustainable development hinges on two critical factors: the subnational implementation of public policies and the efficient allocation of resources across regions through vertical intergovernmental transfers. We introduce a framework that links these two mechanisms for analyzing the impact of reallocating federal transfers in the presence of regional heterogeneity from development indicators, budget sizes, expenditure returns, and long-term structural factors. Our study focuses on the case of Mexico and its 32 states. Using an agent-based computational model, we estimate the development gaps that will remain by the year 2030, and characterize their sensitivity to changes in the states' budget sizes. Then, we estimate the optimal distribution of federal transfers to minimize these gaps. Crucially, these distributions depend on the specific development objectives set by the national government, and by various interdependencies between the heterogeneous qualities of the states. This work sheds new light on the complex problem of budgeting for the Sustainable Development Goals at the subnational level, and it is especially relevant for the study of fiscal decentralization from the expenditure point of view. Highlights: A computational approach to study fiscal transparency in a multidimensional setting. Novel data on more than 100 indicators at the state level. New data on public expenditure at the subnational level. An estimation of the feasibility of the Sustainable Development Goals at the state level.